Antemortem measurements of neurotransmission: possible implications for pharmacotherapy of Alzheimer's disease and depression. Issue 1 (January 1993) - Francis, P T; Pangalos, M N; Stephens, P H; Bartlett, J R; Bridges, P K; Malizia, A L; Neary, D; Procter, A W; Thomas, D J; Bowen, D M
Abstract : Aspartic acid, 5-hydroxyindoleacetic acid, glutamic acid, homovanillic acid and 3-methoxy-4-hydroxyphenylethylene glycol was determined in samples of ventricular fluid from 82 subjects. Laminar distribution of the total number (Bmax value) of serotonin 1A receptors was determined on seven neurosurgical samples of neocortex. Apart from an association in a small subgroup of subjects between homovanillate concentration and corticosteroid medication, no complicating influences of treatment preceding operation were found. The content of the serotonin metabolite alone was significantly reduced in intractable depressive illness (bipolar and major depressive disorders) compared with neurological conditions subdivided into Alzheimer's disease, other dementias and other conditions. There was no other significant difference between these groups for the compounds measured. The total number of serotonin 1A receptors was highest in the superficial layers, being considerably higher than in the rat, irrespective of cortical layer. This part of the study indicated that these receptors are important for regulating activity of human corticocortical glutamatergic neurons. The results are discussed in relation to treating depression with serotonergic agents and targeting corticocortical glutamatergic neurons as well as acetylcholine in Alzheimer's disease.